Mendorong Pemahaman Kritis Tentang Dokumen-Dokumen Prinsipil dan Narasi Kebijakan Luar Negeri Amerika di Kawasan Asia Pasifik 2000-2010: Catatan Penelitian - Sudarman, Suzie (UI Scholars Hub, 2011)
This research note essentially highlights how an argumentation was developed to reveal the implicit tensions that had been part of the American foreign policy maneuvers in Asia-Pacific, and the locus that were expressed have caused controversy. The finding is an effort to formulate analysis of the American foreign policy through an understanding of the nature of paradoxal and tension in the general American foreign policy, specifically in Asia-Pacific. Moreover, the pressures from outside the Asia-Pacific region, have eventually impacted the configuration of the publik officers and the experienced politicians in the locale, who have resulted policies to support the establishment of the relevant institutions in the region.